KEBIJAKAN PEMERINTAH URUGUAY MELANGGAR HASIL KONVENSI TUNGGAL 1961 BERKAITAN DENGAN NARKOTIKA DAN PSIKOTROPIKA - Edward Rivaldo. S; Idjang Tjarsono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This study aims to explore the Uruguayan Government policy violates the 1961 Single Convention results relating to narcotic drugs and psychotropic substance, to knowing the implications that will be brought about by the Uruguay Government policy legalizing cultivation, distribution and consumption of cannabis/Marijuana trade international and to find out the extent to which the role of The International Narcotics Control Board (INCB).This study used qualitative research methods which the source data was taken from books, journals, newspapers, internet, and previous research has relevant data with the title. The concept used in this study is the concept of national interest and the theory of Rational Actor. By using Nation - State level behavior analysis, the main focus is to study the behavior of states in getting its interests in international relations.This study will describe Uruguay Government’s violated The Single Convention of 1961 relating to narcotics and psychotropic. Uruguay Government made a policy which every citizen’s can produce and use narcotics and psychotropic freely. Uruguay Government made a Legalization Cannabis/Marijuana. The policy Uruguay Government’s was contradiction with the Single Convention of 1961 about narcotics and psychotropic. Regulation No. 19.172 really contradiction with Article 2 section 9, Article 4, and Article 36. The result of The Single Convention 1961 decided that utilising narcotics and psychotropic just for medhical necessity and scientific research.Keywords:Legalization, Policy Uruguay Goverment’s, The Single Convention of 1961, narcotics and phsycotropic